Sequential pattern mining on library transaction data - Sitanggang, Imas Sukaesih; Husin, Nor Azura; Agustina, Anita; Mahmoodian, Naghmeh (IEEE, 2010)
Application of data mining techniques in library data results interesting and useful patterns that can be used to improve services in university libraries. This paper presents results of the work in applying the sequential pattern mining algorithm namely AprioriAll on a library transaction dataset. Frequent sequential patterns containing book sequences borrowed by students are generated for minimum supports 0.3, 0.2, 0.15 and 0.1. These patterns can help library in providing book recommendation to students, conducting book procurement based on readers need, as well as managing books layout.